2007
DOI: 10.1161/hypertensionaha.107.090092
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Chronic Ventricular-Arterial Coupling in Systole and Diastole

Abstract: Abstract-Aging and hypertension lead to arterial remodeling and tandem increases in arterial (Ea) and ventricular (LV) systolic stiffness (ventricular-arterial [VA] coupling). Age and hypertension also predispose to heart failure with normal ejection fraction (HFnlEF), where symptoms during hypertensive urgencies or exercise are common. We hypothesized that: (1) chronic VA coupling also occurs in diastole, (2) acute changes in Ea are coupled with shifts in the diastolic and systolic pressure-volume relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 47 publications
1
51
0
1
Order By: Relevance
“…An early report demonstrated a reduced N2BA:N2B ratio in a limited number of HFpEF versus HFrEF patient hearts 6 and a follow-up study showed an increased ratio in advanced HFpEF compared with nonfailing donor hearts. 111 In contrast, a hypertensive dog model with diastolic dysfunction revealed a reduced cardiac N2BA:N2B ratio versus healthy dogs 116,117 and slightly decreased N2BA proportions appeared in the spontaneously hypertensive Figure 5. Directions, causes, and consequences of titin-isoform switching in the heart.…”
Section: Adjustment Of Titin Stiffness By Isoform Switching In Nonfaimentioning
confidence: 91%
“…An early report demonstrated a reduced N2BA:N2B ratio in a limited number of HFpEF versus HFrEF patient hearts 6 and a follow-up study showed an increased ratio in advanced HFpEF compared with nonfailing donor hearts. 111 In contrast, a hypertensive dog model with diastolic dysfunction revealed a reduced cardiac N2BA:N2B ratio versus healthy dogs 116,117 and slightly decreased N2BA proportions appeared in the spontaneously hypertensive Figure 5. Directions, causes, and consequences of titin-isoform switching in the heart.…”
Section: Adjustment Of Titin Stiffness By Isoform Switching In Nonfaimentioning
confidence: 91%
“…Left ventricular tissue of normal adult dogs was sampled as described. 25 All procedures were conducted in full accordance with the institutional guidelines and were approved by the respective ethics committees. …”
mentioning
confidence: 99%
“…However, we could not assess perivascular fibrosis in coronary arteries as is possible in rodents with prominent intramyocardial coronary arteries. In this elderly hypertensive model, there is elastin degradation, increased collagen, and decreased collagen solubility in the aorta, 10 and these pre-existing age-and hypertension-related changes may modify the large artery response to MC excess.…”
Section: Discussionmentioning
confidence: 98%